Dual‐responsive crosslinked micelles of a multifunctional graft copolymer for drug delivery applications. Issue 9 (1st May 2017) - Lin, Shudong; Feng, Shiting; Mo, Yangmiao; Tu, Yuanyuan; Guo, Yu; Hu, Jiwen; Liu, Guojun; Zhong, Zhiwei; Miao, Lei; Zou, Hailiang; Liu, Feng
ABSTRACT: A novel multifunctional amphiphilic graft copolymer has been synthesized consisting of a biodegradable poly(l ‐aspartic acid) backbone that was decorated by water‐soluble poly(ethylene glycol) (PEG) and pH‐responsive poly( N, N ‐diethylaminoethyl methacrylate) (PDEAEMA) side‐chains as well as thiol pendant groups. This graft copolymer together with doxorubicin (DOX) formed micelles in water at pH = 10.0 with PDEAEMA and DOX acting as the core and PEG serving as the micellar corona. Upon oxidation, the thiol groups dimerized to form disulfide bonds, thus "locking in" the micellar structure. These crosslinked micelles expanded as the pH was decreased from 7.4 to 5.0 or upon the addition, at pH = 7.4, of glutathione (GSH), a thiol‐containing oligopeptide that is present in cancerous cells and cleaves disulfide bonds. At pH = 5.0, GSH addition triggered the disassembly of the micelles. The expansion and disassembly of the micelles have been determined via in vitro experiments to evaluate their DOX release behavior. More importantly, the graft copolymer micelles could enter cells by means of endocytosis and deliver DOX to the nuclei of ovarian cancer BEL‐7402 cells. Thus, this polymer and its micelles are promising candidates for drug delivery applications. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 1536–1546 Abstract : A novel micelle with pH and reduction dual sensitivity formed based on a welldefined multifunctional amphiphilic graft copolymer P[Asp(MEA)‐ r ‐Asp(PEG)‐ r ‐Asp(PDEAEMA)‐ r ‐Asp(HMTPA)] was developed. Drug leakage can be avoided in micelle storage and significantly reduced in blood circulation, whereas a burst release of drug was triggered in an acidic and reductant‐enriched environment such as in lysosomes. Cell studies revealed this polymer and its micelles are promising candidates for drug delivery applications.